Thyroid Function Testing - Brent, Gregory A.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2010)
Thyroid function tests are performed by essentially all medical practitioners across every clinical setting. Significant insights have been gained into thyroid regulation and thyroid hormone metabolism that influence the selection and interpretation of thyroid function tests. Recent studies are summarized showing that genetic variations in key thyroid regulating genes may influence thyroid function tests. The basics of thyroid function measurements, approaches, limitations and clinical applications will be described for the major categories of thyroid function tests. Application of thyroid function testing to key clinical settings are discussed, including management of thyroid diseases. An approach to thyroid function testing in special groups is described, including infants and children, the elderly, pregnant women, and the hospitalized patient. The authors represent leaders in research and clinical practice from world class centers of excellence in medicine. "In this volume, leading experts provide a comprehensive overview of a difficult and commonly encountered clinical challenge--how to interpret thyroid function test results. Ranging from fundamental genetics to both inpatient and outpatient environments, this book will be of enriching value to internists, pediatricians, endocrinologists and those studying thyroid physiology." - Shlomo Melmed, M.D. Series Editor.
Thyroid Hormone Metabolism -- Genetic Influences on Thyroid Function Tests -- Influence of Iodine Deficiency and Excess on Thyroid Function Tests -- Regulation of Thyroid Hormone Production and Measurement of Thyrotropin -- Measurements of Thyroxine and Triiodothyronine -- Thyroid Autoantibody Measurement -- Thyroglobulin Measurement -- Thyroid Function Testing in Ambulatory Practice -- Assessing Thyroid Function in Infants and Children -- Assessing Thyroid Function in Hospitalized Patients -- Assessing Thyroid Function in Pregnancy -- Assessing Thyroid Function in the Elderly -- Influence of Drugs on Thyroid Function Tests.
Keywords: Endocrinology .; Internal medicine; General practice (Medicine).; Cardiology; Endocrinology; Internal Medicine; General Practice / Family Medicine; Cardiology